Notes biographiques sur les fondateurs et les guides spirituels des sectes syncrétiques au Gabon - Swiderski, Stanislaw (Anthropologica, 2022)
In Gabun, religious syncretism as a spontaneous popular movement began around 1920, sparked by the social unbalance of the Fang people. This syncretism, inasmuch as it was a mixture of traditional cult elements and elements of Christian cult, was to serve first of all as a means of re-integrating the cult of these people. Today, however, it may be considered as the first step towards the creation of an African Christianism. The Fang people have adapted two cults: the skull cult called Bouiti which was founded by the Pygmies, developed by the Mitsoghos and the Apindjis and brought by them into the region of Lambarene and Libreville; and the Ombwiri cult, created by the peoples known as N’Komi and Miene around Lake Como and gradually established in the Gabun estuary. Today, there are several dozen Bouitist and Ombwirist sects having for origin the particular visions of their founders and the specific circumstances of their religious calling. It is to be noted that the religious personality of these founders and spiritual guides was formed under the influence of a number of factors of social, political, cultural, religious and psychological nature. The appearing of founders of sects may be considered the consequence and proof of the people’s sufferings and aspirations, crushed as they were by French colonization, alienated by occidental culture and religion and crushed by the materialistic civilization of the White race.